Magnetospheric Multiscale Observations of Turbulent Magnetic and Electron Velocity Fluctuations in Earth's Magnetosheath Downstream of a quasi-parallel bow shock. (October 2018) - Pollock, C.J.; Burch, J.L.; Chasapis, A.; Giles, B.L.; Mackler, D.A.; Matthaeus, W.H.; Russell, C.T.
Abstract: We present statistical single-spacecraft observations of magnetic and electron velocity fluctuations in Earth's magnetosheath, likely in the vicinity of the magnetopause, downstream of a bow shock immersed in quasi-parallel interplanetary magnetic field conditions, a situation conducive to plasma turbulence in the downstream flow. These fluctuations exhibit scale-dependent behavior, wherein histograms of their Partial Variance of Increments (PVIB or PVIVe) demonstrate highly non-Gaussian forms at small scales and are reasonably well-described by kappa distributions, albeit with fitted values of the kappa parameter only slightly larger than 1.5, exemplifying their power law nature at large values of PVI. At larger scales, the PVI histograms lose their non-Gaussian nature and are well described by both Gaussian and kappa distributions with large values of the kappa parameter. The PVI histograms furthermore exhibit kurtosis that increases with decreasing scale, a characteristic that is much more prominent in the magnetic fluctuations than in the electron velocity fluctuations. This feature that is not yet explained. In both cases, the results are characteristic of turbulent intermittency. Highlights: First PVI analysis of electron velocity fluctuations in turbulent space plasma. PVI of electron velocity and magnetic field fluctuations show scale-dependence. Kappa function fits PVIs well at all scales; Gaussian fits well only at large scales.